Experimental Investigation of Factors Influencing Operating Rotor Tip Clearance in Multistage Compressors - Reid A. Berdanier; Nicole L. Key (International Journal of Rotating Machinery)
An analysis of compressor rotor tip clearance measurements using capacitance probe instrumentation is discussed for a three-stage axial compressor. Thermal variations and centrifugal effects related to rotational speed changes affect clearance heights relative to the assembled configuration. These two primary contributions to measured changes are discussed both independently and in combination. Emphasis is given to tip clearance changes due to changing loading condition and at several compressor operating speeds. Measurements show a tip clearance change approaching 0.1 mm (0.2% rotor span) when comparing a near-choke operating condition to a near-stall operating condition for the third stage. Additional consideration is given to environmental contributions such as ambient temperature, for which changes in tip clearance height on the order of 0.05 mm (0.1% rotor span) were noted for temperature variations of 15°C. Experimental compressor operating clearances are presented for several temperatures, operating speeds, and loading conditions, and comparisons are drawn between these measured variations and predicted changes under the same conditions.